1988
DOI: 10.1017/s0305000900012599
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and linguistic factors in the development of word definitions

Abstract: Three studies were carried out in order to account for development of word definitions. Study 1 was aimed at analysing the role of class inclusion skills and age (5-and 7-year-olds and adults) in production of definitions containing superordinate categorical terms. No differences were found between 7-year-olds who had passed a class inclusion task and those who had not passed it as regards number of definitions containing superordinates, while differences were found between younger and older children and betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1
9

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 15 publications
5
30
1
9
Order By: Relevance
“…For example, "An apple is to eat" (Litowitz, 1977). This early inclination towards functional responses has also been observed in other studies (e.g., Benelli et al, 1988;Nelson, 1978;Wehren et al, 1981). Wehren et al (1981) studied the definitional responses produced by 80 English-speaking preprimary and primary school children and 20 adults and reported that the youngest children tended to provide functional responses, while the older children were more likely to include descriptions of external appearance or perceptual characteristics of the reference (e.g., "A plane is white in colour").…”
Section: Contentsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, "An apple is to eat" (Litowitz, 1977). This early inclination towards functional responses has also been observed in other studies (e.g., Benelli et al, 1988;Nelson, 1978;Wehren et al, 1981). Wehren et al (1981) studied the definitional responses produced by 80 English-speaking preprimary and primary school children and 20 adults and reported that the youngest children tended to provide functional responses, while the older children were more likely to include descriptions of external appearance or perceptual characteristics of the reference (e.g., "A plane is white in colour").…”
Section: Contentsupporting
confidence: 88%
“…Benelli, Arcuri, and Marchesini (1988) found that the primitive definition form occurring in their young Italian preschoolers usually consisted of a list of associated objects or exemplars as an extension of the definition (e.g., Question: "What is a plane?" Answer: "In the airport" or "A ship").…”
Section: Contentmentioning
confidence: 99%
“…First, the task of defi ning animals was indeed hard for the individuals with WS, particularly at the more sophisticated levels expected of older individuals (cf. Benelli et al, 1988). Second, as assessed by the sorting task, individuals with WS have poorer lexical semantic knowledge than expected given their level of receptive vocabulary, a skill for which this population is noted.…”
Section: Fractionationmentioning
confidence: 92%
“…The ability to formulate these relationships by means of language requires cognitive maturity and semantic knowledge as well as familiarity with a conventional syntactic form for definitions. It is for this reason that word-definition tasks have long been used by test makers and researchers to measure and investigate different aspects of an individual's cognitive, linguistic and metalinguistic development (Al-Issa, 1969;Benelli, Arcuri, & Marchesini, 1988;Bialystok & Majumder, 1998;Kikas, 1993;Litowitz, 1977;Markowitz & Franz, 1983McGhee-Bidlack, 1991;Nippold, 1995;Skwarchuk & Anglin, 1997;Snow, 1990;Watson, 1985Watson, , 1995Wilson, 1975). Consequently, a number of coding systems have been employed to help researchers analyze the word-definition data.…”
Section: Introductionmentioning
confidence: 99%